Across cultures and continents cross-cultural exchange of ideas - Adorján, Boglárka (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The Hungarian educational Research Journal (HeRJ) is the journal of Hungarian educational researchers association of Hungarian educational researchers (HeRA) has published a quarterly English-language The last issue of the 2014 edition of this online journal, published in English since quarterly, focuses on non-European types of education and The last issue of the journal is organized around a rich set of themes, which is the organizing principle that runs through the entire issue throughout the journal...